World War I and the Jews : conflict and transformations in Europe, the Middle East, and America - Rozenblit, Marsha L., 1950-; Karp, Jonathan, 1960- (Berghahn Books, 2017)
World War I utterly transformed the lives of Jews around the world: it allowed them to show their patriotism, to dispel antisemitic myths about Jewish cowardice, and to fight for Jewish rights. Moreover, and especially in Eastern Europe, Jews suffered tremendously as refugees and deportees, and had to cope with the challenges created by the rebordering of Europe and the creation of new states after the war. This book provides a fascinating survey of the ways in which Jewish communities participated in and were changed by the Great War, focusing on the dramatic circumstances they faced in Europe, North America, and the Middle East during and after the conflict.